Limitations and Success Factors of Female Entrepreneurship: A Costa Rican Perspective - Sandoval Álvarez, Carlos (2023)
We deepen into the life stories of renowned women entrepreneurs to uncover the motivations, constraints, and success factors of the emergence of successful female entrepreneurship. Three in-depth interviews on well-known and successful Costa Rican women entrepreneurs were conducted by means of narrative techniques. Our findings provide empirical evidence suggesting that the motivations of very successful women entrepreneurs are universal. Besides, the constraints of very successful female entrepreneurs are diverse, from which the need of financial support, the lack of strategic planning, the bureaucracy lack of knowledge in marketing, the reaction of competitors, stand out as relevant constraints. Furthermore, our study reveals that intangible factors, that is, human and social capital, are fundamental to growth and consolidation of companies created and managed by women. Finally, our results suggest that women entrepreneurs prefer to measure their entrepreneurial success through emotional and personal aspects rather than through financial or market metrics.